PENANGANAN PENGEMBALIAN KEPERCAYAAN INVESTOR MELALUI MANAJEMEN KRISIS OLEH BADAN PENGUSAHAAN BATAM - Barlian, Tria Dara; Hafiar, Hanny; Fatma S, Diah (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
As of the biggest tax report contributor in Indonesia, Batam is one of the advance city, but Batam is not guaranteed free from obstacles and barriers which blocked the investment activity in Batam. This obstacle inter alia is a lot of demonstration activity in Batam. Those protesters wreck the public facilities, main road, police office, and the investor’s company. These anarchy activities make the investor become worried and questioning BP Batam effort to handle this situation. BP Batam already did some effort to muffle the demonstration that happen in Batam but the demonstration is still going on until now. That’s why researcher choose topic. The focus on the study: How’s the Crisis Management on the Handling of Demonstration Issue Among Investor by the Batam Indonesia Free Zone Authority. This research used qualitative approach with the constructivism paradigm and case study form of study. The subjects were BP Batam officials. Data were collected through in depth interview, passive participant observation, literature study, documenter study, and online data tracing. Using symbolic interactionism as theory by George Herbert Mead. The result of this research revealed that issue management aspect which is conducted by the Batam Indonesia Free Zone Authority when demonstration strike for investor, first BIFZA will call the authority to execute securing vital objects. After that BIFZA will give information through online media and offline media. The next step is BIFZA organize a business gathering and invite foreign investor and local investor to deliver information related to demonstrations and finally investor gain information about demonstration and BIFZA effort to manage it. The communication pattern that the Batam Indonesia Free Zone Authority did to handle demonstration issue were interacting with it's public.